A efetividade processual e sua celeridade sob o enfoque dos atos processuais no processo eletrônico - Strenger, Guilherme (2014)
This study aims to analyze the principle of reasonable duration of the proceedings towards the so-called effectiveness in contemporary civil procedure. In this sense, the analysis of constitutional principles will support a better understanding of the modern scientism procedure, guided by the obedience to Constitution. Thus, reflections turn over on what represents an expeditious and effective process, so focusing on the reasonable length without sacrificing legal certainty. Also, it is included in the study the Electronic process of law and its sue activities. Thereat, the goal is to evaluate in what ways or points the Electronic process of law and electronic activities in process of law may contribute for the principle of reasonable duration of the proceedings in sue activities. Moreover, it is presented some observations about this up-to-date phenomenon; and finally it is concluded that an expeditious and effective process does not necessarily means that the process of law shall be electronically managed